2018
DOI: 10.1007/s10616-017-0147-7
|View full text |Cite
|
Sign up to set email alerts
|

Anti-cancer effect of Aquaporin 5 silencing in colorectal cancer cells in association with inhibition of Wnt/β-catenin pathway

Abstract: Aquaporin 5 (AQP5) is a water channel protein that is over-expressed in many tumors. Elevated expression of AQP5 is associated with poor prognosis of colorectal cancer. Yet, whether AQP5 plays a role in epithelial-mesenchymal transition (EMT) of colorectal cancer has not been reported until now. Here we aim to investigate the function of AQP5 in the EMT process of colorectal cancer. We transfected HCT116 and SW480 cells with AQP5-specific shRNA and verified the knockdown efficiency through western blotting and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 41 publications
3
15
0
Order By: Relevance
“…44 Inhibition of PAR2 suppresses EMT and promotes the chemo-resistance of CRC to 5-FU. 45 Previous study showed that AQP5 silencing has an anti-cancer effect via regulating Wnt/β-catenin pathway and EMT progress, 46,47 which is consistent with our research. Additionally, AQP5 promotes hepatocellular carcinoma metastasis via modulating NF-κB-regulated EMT progress.…”
Section: Discussionsupporting
confidence: 90%
“…44 Inhibition of PAR2 suppresses EMT and promotes the chemo-resistance of CRC to 5-FU. 45 Previous study showed that AQP5 silencing has an anti-cancer effect via regulating Wnt/β-catenin pathway and EMT progress, 46,47 which is consistent with our research. Additionally, AQP5 promotes hepatocellular carcinoma metastasis via modulating NF-κB-regulated EMT progress.…”
Section: Discussionsupporting
confidence: 90%
“…It was shown that AQP3 was also involved in prostate cancer cell motility and invasion through ERK1/2-mediated matrix metallopeptidase 3 secretion (56). Epithelial cells undergoing EMT gain motility and invasiveness, which are characteristic features of metastatic cells (57), and AQP5 knockdown in various cancer cells indicated that AQP5 overexpression promotes EMT (9,58). However, our data indicate that AQP5 regulation of adhesion proteins in MDCK cells, a noncancerous cell line, is independent of EMT (10).…”
Section: Discussionmentioning
confidence: 69%
“…5e). β-catenin is a key factor that activates upstream and downstream factors of the Wnt/β-catenin signaling pathway (19). The mrna and protein expression levels of β-catenin were also significantly decreased in MCF-7 and Mda-MB-231 cells treated with 400 and 800 µg/ml aPS compared with the control group ( Fig.…”
Section: Aps Inhibits Breast Cancer Cell Invasion Invasion Is Anmentioning
confidence: 87%
“…The present results demonstrated that aPS reduced the expression levels of cytoplasmic and nuclear β-catenin in a dose-dependent manner. additionally, cyclin d1 and c-Myc are produced following β-catenin activation (19). c-Myc, a nuclear protein transcription factor, is associated with the activation of genes that are related to multiple cellular processes, such as proliferation, differentiation, and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation